Conceptual framework development of learning motivation using Augmented Reality and Virtual Reality applications for motorcycle engine assembly - Win, Lai Lai (2022)
Virtual Reality (VR) and Augmented Reality (AR) are rapidly growing research topics in many different fields such as education, training, industries, military, tourism, and many others. In addition, it has become increasingly important for the educational sector as well as other industries to acquire new abilities through implementing the latest technologies in education. This includes engineers, technicians, and workers particularly in assembly and disassembly tasks. According to the majority of practitioners, an innovative method of acquiring information and skills would better meet their need for information and skills required. Unfortunately, students from the Department of Mechanical and Manufacturing Engineering of Universiti Putra Malaysia (UPM) faced difficulty to perform new tasks, specifically for complicated and crucial motorcycle engine assembly tasks. Alternative approaches in learning, are actively explored and investigated since it is essential to reduce students’ assembly time in order to prevent training costs. It can damage the real components and frustrate students when they made a mistake while performing the assembly tasks. The reasons for this problem are lack of information, limited field of view, time-consuming, and lack of guidance regarding how to perform the assembly process. Therefore, there is a need to conduct research on how to overcome these problems. The main aim of this study is to develop a conceptual framework for learning motivation using AR and VR applications to help students with a new method of performing engine assembly task. The AR and VR applications were designed to enhance learning motivation and to create a better and higher-quality engineering practical education system. The HTC Vive and Unreal Engine were used to create a fully immersive VR application. Two AR applications (markerless AR and marker-based AR) were then created using Unity 3D and the EPSON MOVERIO BT-300. A total of 14 engineering students from UPM were asked to complete all four experiments: (1) video-based, (2) marker-less AR, (3) marker-based AR, and (4) VR based. The overall results showed that the marker-less AR application was the best (43%) followed by the VR based method (42%). The marker-based AR method was at 3rd place which was only 28% better, than the existing video-based method (4th place). Then, the framework was developed depending on the result of all VR and AR applications. The developed learning motivational conceptual framework has been validated by seven international VR and AR experts. Based on the evaluation of the framework, 86% of the experts strongly agreed that the framework provides clear guidance and covers every step of the engine assembly process with AR and VR applications. In addition, 100% of experts agreed that the overall information of the framework is straightforward guidance and suitable for use in automobile engine assembly for VR and AR applications to motivate the learning process. Therefore, the developed framework will be shared with universities and practitioners. This framework can serve as a guidance for them in order to achieve reasonable costing, minimize assembly time and errors, and ultimately improve their learning motivation and performance.